A low-cost, high-quality method for remote recording of presentations - Tan, L.K.; Wong, J.H.; Ng, K.H. (American Roentgen Ray Society (ARRS), 2006)
OBJECTIVE: The purpose of this article was to develop a low-cost method for high-quality remote capturing and recording of multimedia presentations. CONCLUSION: The method for making high-quality digital recordings of presentations by using the mix of freely available software presented in this article offers great potential for institutions on a budget as well as others seeking viable alternatives to current methods of presentation recording.